Unpublished stela of a couple of a priestess and a soldier from Thamugadi - Bouder , Amel (The Algerian Historical Journal, 2026)
In this article, we propose to make an iconographic study of a funerary stele from the city of Timgad, the ancient Thamugadi. This stele was the subject of a doctoral study in 1983 (Hammoutene, 1983, pp. 66-67, n° IA.12, fig. IA.12 ) , but it has never been published and has remained unknown to the scientific community. Its importance lies in the fact that it sheds light on the composition of the Roman city of Thamugadi. Furthermore, the iconographic scheme carved on the stele is one of the rarest in the region and it happens to have its parallels in the rest of the Roman Empire, which is why we will make a comparative study with